Applying Research to a Realized Theatrical Design - Thorpe, Kathalina P. (My University, 2020)
“All aspects of a scenic designer’s work can be approached as craft. The challenge is to recognize the importance of the decisions that need to be made. Even the most intangible, can be approached with craft. The study of the text, research, and conceptual thinking are skills best practiced and mastered with planning thoroughness, and purpose.” -- Robert Klingelhoefer. For the production of Truth and Other Lies this February, I had to work with both the tangible and intangible parts of the craft. I was able to utilize trial and error approaches to many design elements while still holding on to research elements and director values. The importance of sharing this process is to show how much deeper the art of theater goes. It is not a simple create and perform process. There are countless hours of research and elegant solutions to be had. My presentation will give a tangible breakdown and understanding of this process through scenic models, renderings, image research, and photos of the realized production.